Equitable Access to Education in Indonesia: A Systematic Review of the Literature with Bibliometric Analysis (2007-2025) - Farhan Apriliansyah; Teguh Trianung Djoko Susanto; Linda Ika Mayasari; Kamaludin Kamaludin (FKIP - Universitas Riau, 2026)
Equitable access to education remains a key priority of Indonesia’s national education policy. Various government initiatives, including the Smart Indonesia Program (PIP), the New Student Admissions (PPDB) zoning system, and educational development in 3T regions, have been implemented to reduce educational disparities. This study aims to analyze the development and research trends related to equitable access to education in Indonesia during 2007-2025 through a systematic literature review combined with bibliometric analysis. A total of 155 articles published between 2007 and 2025 were selected based on predefined inclusion criteria using the PRISMA approach and analyzed using VOSviewer. The results reveal a significant increase in publications, particularly during 2020–2021 and 2024-2025. The dominant research themes include policy implementation, educational infrastructure, zoning policies, and digital transformation. Network visualization indicates strong thematic relationships among educational equity, access, policy, and basic education. The findings show that educational policies have contributed positively to expanding access, with 78% of the analyzed studies reporting improvements in educational access. However, equitable quality remains a major challenge, as 89% of the studies identified disparities in school quality, teacher distribution, and educational facilities. Future research should focus on underserved regions, longitudinal approaches, advanced analytical methods, and the integration of access and quality dimensions to support sustainable educational equity in Indonesia.